INTEGRASI NILAI-NILAI ISLAM DALAM PRAKTIK MANAJEMEN BISNIS MODERN - Fitrayani, Fitrayani (PILAR, 2025)
This study aims to analyze the relevance and contribution of Islamic values in modern business management practices through a literature review approach. Fundamental values such as amanah (trust), shura (deliberation), shidq (honesty), and 'adl (justice) are studied conceptually and associated with contemporary management principles. The results of the study indicate that the integration of Islamic values not only strengthens the ethical dimension in managerial decision making, but also encourages organizational sustainability, accountability, and social harmony in the business world. This study confirms that Islamic values have high compatibility with modern management approaches and can be the basis for the formation of moral, inclusive, and long-term oriented business governance. The implications of this study open up space for further empirical research in the context of Islamic and conventional business industries and organizations.